Perception Of Customers About Celebrity Endorsement Process And Its Subsequent Impact On Customers’ Purchasing Decisions - Amos Ojo Adedeji (Cita konsultindo, 2023)
Advertising is a key to log into a great exploit in business. It has been widely used with various methods by one business or the other to outshine one another. Celebrity endorsement stands tall as one the strategies of advertisement in this modern day business. However, taking right decision is essential. The study qualitatively interrogate the perception of consumer on celebrity endorsement process, the effect of celebrity endorsement on the attitude change of customer and its impact on purchasing decision. The paper revealed successful endorsement when there is link between the celebrity and the endorsed product, endorsed product will be of higher value and of higher demand, expensive products endorsed by expert stand chance to be purchased unendorsed product, celebrity endorsements are more of national than local market products, and highly educated customers are less influenced than less educated customer by any endorser among others. Low knowledge of perceptions, mix-match role of celebrity, no or little knowledge of the integration of celebrity endorsement and hidden performance decline were also noted as challenges that hinder customer from taken right purchasing decision. The paper recommended a critical study of perceptions by customers, maxing of celebrity assigned role with product, and understanding of integration of celebrity endorsement. Familiarity of selected celebrity with the market is also apt